2020
DOI: 10.1080/09658211.2019.1710216
|View full text |Cite
|
Sign up to set email alerts
|

Does retrieving a memory insulate it against memory inhibition? A retroactive interference study

Abstract: Several recent studies suggest that an initial retrieval attempt imbues retrieved memories with special resilience against future interference and other forgetting mechanisms. Here we report two experiments examining whether memories established through initial retrieval remain subject to retrieval-induced forgetting. Using a version of a classical retroactive interference design, we trained participants on a list of A-B pairs via anticipationconstituting a form of retrieval practice. After next training parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
(159 reference statements)
0
8
0
Order By: Relevance
“…(Though recent evidence suggests that inhibition also plays a role in this paradigm. Hulbert & Anderson, 2020).…”
Section: Significant Suppression-induced Forgetting In Healthy Adultsmentioning
confidence: 99%
“…(Though recent evidence suggests that inhibition also plays a role in this paradigm. Hulbert & Anderson, 2020).…”
Section: Significant Suppression-induced Forgetting In Healthy Adultsmentioning
confidence: 99%
“…Some research has suggested that interference may be modulated by inhibiting competitors at retrieval (Anderson, 2003; Anderson et al, 1994; Hulbert & Anderson, 2020). For example, proactive interference could be resolved by temporarily inhibiting previously learned information that competes for retrieval of the newly learned information.…”
Section: Intraobject and Extraobject And Memory Binding Across Develo...mentioning
confidence: 99%
“…It is unclear whether interference will be exacerbated more by blocked or interleaved presentation. Reactivating prior knowledge protects this information from interference from new, related information (retroactive interference; Hulbert and Anderson, 2020), and even can promote acquisition of related information (facilitation; Kuhl et al, 2010;van Kesteren et al, 2018). Furthermore, reactivation ease has been linked to strength of the memory , suggesting that participants may more easily reactivate information during blocked presentation and, as a result, have reduced interference or enhanced facilitation, both of which would enhance learning.…”
Section: Memory For Related Informationmentioning
confidence: 99%
“…Furthermore, specific features of blocked presentation also support my prediction that memory retention will be enhanced by this presentation format. I predict that the relationship between stronger prior knowledge and better acquisition of related information (Kuhl et al, 2010;van Kesteren et al, 2018), as well as greater protection from distortion of prior knowledge when related information is encountered (Hulbert and Anderson, 2020), will make strength of prior knowledge the most important factor that affects memory for related information.…”
Section: Memory For Related Informationmentioning
confidence: 99%